1982
DOI: 10.1152/ajpheart.1982.243.6.h837
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic depression of microcirculation, central hemodynamics, and respiration in decerebrate rats

Abstract: The objectives of this study were the development of a skeletal muscle microcirculatory preparation, in which the complications of drug anesthesia were minimized, and the quantitation of the effects of urethan and chloralose anesthesia on the microcirculation. Rats were initially anesthetized with urethan and chloralose and decerebrated by a midcollicular transection. The cremaster skeletal muscle, with intact circulation and innervation, was prepared for intravital microscopy by placement in a tissue bath. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…This is in general agreement with what has been found to be true for arteriolar vasomotion in both connective tissue [12] and skeletal muscle [17], One implication of this lack of clear correlation between vessel size and vasomotion might be that the mechanisms un derlying vasomotion are of a uniform type in the range of vessel diameters investigated and that force production (number of muscle elements) grows approximately in pro portion with the vessel wall tension according to Laplace's law. However, Colantuoni et al [18] found that, in the hamster skin fold preparation, the vasomotion frequency decreased from a maximum of 9-15 cpm in 8-to 15-pm A4 arterioles to 1-3 cpm in 70-to lOO-pm Ai small arter ies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in general agreement with what has been found to be true for arteriolar vasomotion in both connective tissue [12] and skeletal muscle [17], One implication of this lack of clear correlation between vessel size and vasomotion might be that the mechanisms un derlying vasomotion are of a uniform type in the range of vessel diameters investigated and that force production (number of muscle elements) grows approximately in pro portion with the vessel wall tension according to Laplace's law. However, Colantuoni et al [18] found that, in the hamster skin fold preparation, the vasomotion frequency decreased from a maximum of 9-15 cpm in 8-to 15-pm A4 arterioles to 1-3 cpm in 70-to lOO-pm Ai small arter ies.…”
Section: Discussionsupporting
confidence: 89%
“…However, it appears to have a lower frequency than the vasomotor activity seen in skeletal muscle, such as the rabbit tenuissimus muscle (5-32 cpm) [14,15], bat coracocutaneous muscle (24-75 cpm) [16] and the rat cremaster muscle (25-35 cpm) [17].…”
Section: Discussionmentioning
confidence: 99%
“…18 > 19 The frequency of vasomotion we observed was between 5 and 8 cycles/min, which agrees with previous observations in small arterioles in the hamster skinfold preparation. 20 Higher frequencies of vasomotion were reported in the skeletal muscle of decerebrated 21 or pentobarbital-anesthetized rat, 22 whereas much lower frequencies were reported in the cerebral microcirculation of awake rabbits. 23 Apart from an influence of anesthetics, the pattern of vasomotion may vary for different arterioles.…”
Section: Discussionmentioning
confidence: 98%
“…We developed the DPP as an alternative to, rather than a replacement of, previous preparations because it 1) allows the study of respiratory chemosensitivity independent of heart rate and systemic blood pressure, 2) allows the use of rats, which are being used increasingly as an experimental model for studies of the control of breathing, and 3) increases the feasibility of addressing a greater range of questions, owing to the fact that the DPP requires less sophisticated surgery and can be prepared rapidly. Being decerebrate, the DPP avoids the nonspecific, depressive effects of anesthetics and paralytic agents on respiratory chemoreceptors (28,72). Although most of the other preparations used for these kinds of studies are perfused with blood, the DPP is distinct in that the brain stem and the carotid body are artificially perfused with defined media.…”
Section: Critique Of the Dppmentioning
confidence: 99%